Greece in the 21st Century : The Politics and Economics of a Crisis - Dimoulas, Constantine; Fouskas, Vassilis K. (London : Routledge, 2018)
"For most of the first part of the 21st century Greece has been seen as a critical battlefield for the survival of the powerful and the adjustment or extinction of the weak, as if all the historical contradictions of the global financial crisis and the eurozone crisis were concentrated in that tiny part of the world, with a population of just 11 million people and a GDP of less than 2% of that of the European Union as a whole. While the country has been overpowered by the disciplinarian and deeply authoritarian policy mix of ordoliberal/neoliberal rules, as this book attempts to show, there is hope. Defeat does not end the crisis, and crisis means constant opportunity. In this state of affairs, all types of agencies try to take advantage of the conditions and opportunities in order to advance towards positions of power and provide the best of solutions for the class interests they represent. Thus, harsh conflict is inevitable and if history provides a yardstick, it is that in periods of conflict and crisis, the winner, usually, is the one who manages to strike the right political and social alliances at the right time.The editors have assembled in this volume a number of interdisciplinary chapters and arguments which, despite their differences, share the strategic aim of a critique of both neoliberalism/ordoliberalism and new authoritarianism. Chapters examine the eurozone crisis from a variety of angles with reference to Greece, and Greek politics and society. With this collection of heterodox and scholarly essays, the authors and editors aim to offer a progressive understanding of current historical circumstances.Constantine Dimoulas is an Assistant Professor in social administration and evaluation of social programmes at Panteion University, Greece.Vassilis K. Fouskas is Professor of international politics and economics at the University of East London, UK, and the founding editor of the Journal of Balkan and Near Eastern Studies (Taylor & Francis)."--Provided by publisher.
chapter Introduction and Acknowledgments: What$1 (Bs in the Greek Cauldron? /s Vassilis K. Fouskas -- chapter 1 Eurozone Authoritarianism and the Neoliberal Project in Greece and Southern Europe / Kees van der Pijl -- chapter 2 Sovereign Debt or Balance-of-Payments Crisis? -- Exploring the Structural Logic of Adjustment in the Eurozone / Matthias Kaelberer -- chapter 3 Greece and the Crisis of the Eurozone: A Structural Analysis / Leila Simona Talani -- chapter 4 Is There Really a Eurozone Crisis? / Turan Subasat -- chapter 5 Competing Explanations and Strategies for the Greek Crisis and the Question of the Productive Model / Stavros Mavroudeas -- r Maria Markantonatou -- chapter 8 The Political Effects of the Greek Economic Crisis: The Collapse of the Old Two-Party System / Alexander Kazamias -- chapter 9 Blaming the Other: An Enquiry into the Cultural and Political Preconditions of the Greek crisis / Tolis Malakos.
Keywords: Greece -- Economic conditions -- 21st century; Greece -- Politics and government -- 21st century